Investigation of AA6063-based metal–matrix composites reinforced with TiO2 dispersoids through digitally assisted techniques for mechanical, tribological, and microstructural characterizations - Pattar, Jagannath; Ramesh, Dasappa; Malghan, Rashmi Laxmikant; Kumar, Ajay; Kumar, Pawan; H. M., Vishwanatha (Frontiers in Mechanical Engineering, 2024)
In the current investigation, an aluminum metal matrix composite (AMMC) developed by dispersing TiO2 dispersoids, in different volume fractions, into the AA6063 matrix via stir casting technique, is subjected to process-structure correlation studies. Four different samples in weight-to-weight ratio were 99Al-1TiO2, 97Al-3TiO2, and 95Al-5TiO2 and as-received AA6063. The mechanical properties— microhardness, tensile strength, and tribological behaviour, were analyzed followed by microstructure analysis. It was observed that the addition of 5%TiO2 particles enables the AA6063 matrix to accommodate higher strain energy and provides the required driving force for the generation of dislocations and substructures. Therefore, considering the plastic deformation, the ultimate tensile strength (σ_ut) increased gradually with the addition of TiO2 in weights %. The flow curves of 95Al-5TiO2 envisage the highest value of σ_ut while the as-received AA6063 exhibited the lowest. When the linear elastic deformation was considered, the AA6063 showed the lowest yield strength (σys) as compared to AMMC samples for all TiO2 weight %; however, the variation in σys among AMMC samples was minimal. The microhardness of the samples was increased gradually with the addition of TiO2 and the % reduction in area at the fracture was largest for 95Al-5TiO2. Taguchi’s L9 array and analysis of variance (ANOVA) technique envisage that the % contribution of normal load was highest followed by weight % of TiO2 and speed to the material wear. The sliding speed exhibited the least contribution among all process parameters. The wear surface characteristics like micro-voids, delamination, micro-cracks, and wear debris are observed for most of the samples with a varying extent, qualitatively. The overall improvement in the strength is attributed to the effect of the addition of the dispersoids. During the solidification of the melt, the grain growth was surpassed/pinned by the TiO2 particles which hindered the grain growth resulting in grain size refinement.